An independent external validation and evaluation of QRISK cardiovascular risk prediction: a prospective open cohort study - Collins, G; Altman, D (2009)
OBJECTIVE: To independently evaluate the performance of the QRISK score for predicting 10 year risk of cardiovascular disease in an independent UK cohort of patients from general practice and compare the performance with Framingham equations. DESIGN: Prospective open cohort study. SETTING: 274 practices from England and Wales contributing to the THIN database. PARTICIPANTS: 1.07 million patients, registered between 1 January 1995 and 1 April 2006, aged 35-74 years (5.4 million person years) with 43 990 cardiovascular events. MAIN OUTCOME MEASURES: First diagnosis of cardiovascular disease (myocardial infarction, coronary heart disease, stroke, and transient ischaemic attack) recorded in general practice records. RESULTS: This independent validation indicated that QRISK offers an improved performance in predicting the 10 year risk of cardiovascular disease in a large cohort of UK patients over the Anderson Framingham equation. Discrimination and calibration statistics were better with QRISK. QRISK explained 32% of the variation in men and 37% in women, compared with 27% and 31% respectively for Anderson Framingham. QRISK underpredicted risk by 13% for men and 10% for women, whereas Anderson Framingham overpredicted risk by 32% for men and 10% for women. In total, 85 010 (8%) of patients would be reclassified from high risk (>or=20%) with Anderson Framingham to low risk with QRISK, with an observed 10 year cardiovascular disease risk of 17.5% (95% confidence interval 16.9% to 18.1%) for men and 16.8% (15.7% to 18.0%) for women. The incidence rate of cardiovascular disease events among men was 30.5 per 1000 person years (95% confidence interval 29.9 to 31.2) in high risk patients identified with QRISK and 23.7 per 1000 person years (23.2 to 24.1) in high risk patients identified with Anderson Framingham. Similarly, the incidence rate of cardiovascular disease events among women was 26.7 per 1000 person years (25.8 to 27.7) in high risk patients identified with QRISK compared with 22.2 per 1000 person years (21.4 to 23.0) in high risk patients identified with Anderson Framingham. CONCLUSIONS: The QRISK cardiovascular disease risk equation offers an improvement over the long established Anderson Framingham equation in terms of identifying a high risk population for cardiovascular disease in the United Kingdom. QRISK underestimates 10 year cardiovascular disease risk, but the magnitude of underprediction is smaller than the overprediction with Anderson Framingham.